Making of a border island: The example of Lesvos - Tsitsaraki, Paraskevi; Petracou, Electra (European Journal of Geography, 2023)
This article examines the gradual transformation of the island of Lesvos from a boundary into a border place, where migration management and border policies are pursued with the aim of controlling human mobility. Refugees have been arriving on Lesvos since 2000. This period coincided with the establishment of a common external border under the Schengen Agreement and the attempts to adopt a common asylum policy within the EU. Therefore, in this study we examine the impact of the implementation of certain border management measures on Lesvos, which have resulted in Lesvos being an example of a border that is not a line but an island (Mountz, 2014, 2020). Furthermore, the adoption of various asylum policies has led to the restriction of population mobility and the detention of people, justifying the policy and practice of abolishing asylum protection in the EU. In writing this article, we have drawn on a review of literature, reports from international organisations, legislation, relevant coverage of events in the international and local press, and participant observations. Highlights: EU common asylum policies and external borders. Lesvos as a border island. Abandonment of refugee protection rights.